The Role of Indonesian Language Learning in Developing University Students’ Academic Communication Ethics - Tawakkal, M. Iqbal (International Journal of Multidisciplinary Research and Innovation, 2025)
Academic communication ethics is one of the essential competencies that university students must possess in higher education environments. However, in practice, many students are still unable to use Indonesian politely and in accordance with academic conventions. This issue indicates that Indonesian language learning has not yet been fully optimized in shaping students’ academic communication ethics. This study aims to examine the role of Indonesian language learning in building students’ academic communication ethics at Universitas Nahdlatul Ulama Sunan Giri. The study employed a qualitative approach with a descriptive design. The research subjects consisted of students and lecturers teaching the Indonesian language course. Data were collected through observation, interviews, and documentation, and were analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that Indonesian language learning plays a role in shaping students’ academic communication ethics through the habituation of formal, polite, and objective language use in academic activities. Students demonstrated positive development in both oral and written communication after participating in Indonesian language learning. The role of lecturers as facilitators and language role models also supported the formation of students’ academic communication ethics. The implications of this study suggest that Indonesian language learning needs to be continuously optimized as a means of developing academic communication ethics and strengthening academic culture in higher education.